An unusual case of acquired aplastic anemia following SARS-CoV-2 vaccination: A case report - Smruthi PVS; Hiranmayi Koka; Tarun Kumar Suvvari; R. Mounish Reddy; Sai Tejeswi Godavari; Vimal Thomas (IDCases, 2023)
Aplastic Anemia (AA) is a condition where the body's immune system attacks and destroys the hematopoietic stem cells, leading to pancytopenia and an empty bone marrow. AA can be effectively treated using immunosuppressive therapy or hematopoietic stem-cell transplantation. The damage to stem cells in the bone marrow can be due to several causes, such as autoimmune diseases, medication like cytotoxic drugs and antibiotics, and exposure to toxins or chemicals in the environment. In this case report, we present the diagnosis and treatment of a 61-year-old man who was diagnosed with Acquired Aplastic Anemia, which could have developed following his serial immunizations with the SARS-CoV-2 COVISHIELD viral vector vaccine. The patient received immunosuppressive therapy consisting of cyclosporine, anti-thymocyte globulin, and prednisone, resulting in a significant improvement in his condition.